Neurogenic Hypotension and Bradycardia Modulated by Electroacupuncture in Hypothalamic Paraventricular Nucleus - Tjen-A-Looi, Stephanie C.; Fu, Liang-Wu; Guo, Zhi-Ling; Gong, Yiwei D.; Nguyen, Anh Thi Ngoc; Nguyen, Ai-Thuan P.; Malik, Shaista (Frontiers in Neuroscience, 2022)
Electroacupuncture (EA) stimulates somatic median afferents underlying P5-6 acupoints and modulates parasympathoexcitatory reflex responses through central processing in the brainstem. Although decreases in blood pressure and heart rate by the neural-mediated Bezold-Jarisch reflex responses are modulated by EA through opioid actions in the nucleus tractus solitarius and nucleus ambiguus, the role of the hypothalamus is unclear. The hypothalamic paraventricular nucleus (PVN) is activated by sympathetic afferents and regulates sympathetic outflow and sympathoexcitatory cardiovascular responses. In addition, the PVN is activated by vagal afferents, but little is known about its regulation of cardiopulmonary inhibitory hemodynamic responses. We hypothesized that the PVN participates in the Bezold-Jarisch reflex responses and EA inhibits these cardiopulmonary responses through the PVN opioid system. Rats were anesthetized and ventilated, and their heart rate and blood pressures were monitored. Application of phenylbiguanide every 10 min close to the right atrium induced consistent depressor and bradycardia reflex responses. Unilateral microinjection of the depolarization blockade agent kainic acid or glutamate receptor antagonist kynurenic acid in the PVN reduced these reflex responses. In at least 70% of the rats, 30 min of bilateral EA at P5-6 acupoints reduced the depressor and bradycardia responses for at least 60 min. Blockade of the CCK-1 receptors converted the non-responders into EA-responders. Unilateral PVN-microinjection with naloxone reversed the EA inhibition. Vagal-evoked activity of the PVN cardiovascular neurons was reduced by 30 min EA (P5-6) through opioid receptor activation. These data indicate that PVN processes inhibitory cardiopulmonary reflexes and participates in EA-modulation of the neural-mediated vasodepression and bradycardia.